Comparative analysis of snap techniques in young weightathleters at the initial and training stages of sports training - Shalmanov A.A. ,; Skotnikov V.F. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare general and specific criteria for snatch technique among young weightlifters at the initial (26 people aged 9-12 years) and training (129 people aged 13-17 years) stages of sports training. Methods and structure of the study. The technical skill of the athletes was assessed during official competitions using bilateral video recording. The kinematic and dynamic characteristics of the movement of the CM of the barbell were calculated, on the basis of which the criteria for the technical skill of the athletes were determined. Results and conclusions. It was shown that only five athletes at the initial stage of preparation and eight athletes at the training stage corresponded to the criteria of technique corresponding to the values of the rational way of performing this exercise. The remaining athletes had two or more technical errors. From this we can conclude that coaches do not pay enough attention to developing the correct snatch technique.